Political and ideological background of LSSR KGB activity against antisoviet powers in 1954-1990 - Burinskaitė, Kristina (Lietuvos istorijos studijos, 2010)
Communist ideology not only legitimized the Soviet totalitarian regime but also influenced and defined the basis and direction of KGB activity and legitimized its repressive policy. Inner and international policy targets of the Communist Party were also important to KGB activity, influencing its operational activity and its methods. The Communist Party was also an important player in forming the repression policy that was implemented by the KGB. Also, the Communist Party obliged the KGB to undertake ideological and political education functions.After 1954, inner and international situations of the Soviet Union changed, and this changed the positions of the KGB and its priorities, activities, methods; however, the main targets almost hadn’t changed. Now the KGB paid more attention to the prevention of anti-Soviet activity rather than to physical repression. To implement this task, the KGB used prophylaxis, psychological pressure, and formation of public opinion through the media, as well as ideological and political education of society.Communist ideology had a great influence on KGB operational activity, its understanding, and evaluations of anti-Soviet activity. It was evaluated as class struggle that was initiated by the West, especially by the USA. That is why the KGB paid more attention to specific groups of society such as youth, intelligentsia, former political prisoners and deportees, and tried to control all connections with the West.
Keywords: -